A Reader in Slovak Linguistics Studies in Semantics - Kacala, Ján (Specimina philologiae Slavicae, 1992)
The authors of the articles are Slovak linguists who work within various spheres of linguistics. Represented in the volume are authors who started their scientific activity in the pre-war period, directly or indirectly building on the work of the Prague Linguistic Circle, but soon differentiating themselves and contributing to linguistic theory with original works, as well as a newer generation of linguists who entered linguistics within the last two decades.